Modern MIDI : sequencing and performing using traditional and mobile tools - McGuire, Sam (Focal Press, 2014)
In the last five years, the environment in which the Musical Instrument Digital Interface (MIDI) specification works and the tools that communicate via MIDI have changed dramatically. Modern MIDI: Sequencing and Performing Using Traditional and Mobile Tools gives you all the tools you need to properly and effectively use MIDI in a modern setting, while still incorporating vintage MIDI gear. Exploring typical workflows and techniques for both the studio and the performing environment, this book helps you navigate the changes that mobile computing has made to the way the music producer.